Penerapan Model Pengajaran Langsung dalam Meningkatkan Ketrampilan Operasi Hitung Bilangan Bulat Siswa Tunarungu di SLB Kristinia Bitung - Kalvary Luntungan (Jurnal Ilmiah Wahana Pendidikan, 2020)
This research was conducted with the aim of obtaining an overview of the application of direct teaching models in an effort to improve numeracy skills for deaf students at SLB Kristinia Bitung. The research method used was Classroom Action Research (PTK). The research subjects were deaf students in class IV SLB Kristinia Bitung. The classroom research design model used in this study was the Kemmis and Taggart model with planning, implementation, observation, reflection stages by carrying out three cycles. From the data obtained from this study, it can be concluded that the direct teaching model can: a) Reduce the mistakes of deaf students in the subject matter, especially the reduction operations faced, b) Improve the numeracy skills of Deaf Students in Class IV SLB Kristinia Bitung, c) Motivating Students in learning other than studying at school. This means that at home students tend to always want to learn rather than play because there is a teacher who directs them, d) The results achieved by children with dyscalculia in class IV SLB Kristinia Bitung, after the action is sufficiently increased from the ability of 1 time reduction surgery borrowing techniques from 38% - 50% increased to 100%, 2 times the borrowed technique from 30% - 40% increased to 100% and 3 times the borrowed technique from 30% to 90%. By looking at the results achieved by the students, it means that it can be concluded that the direct teaching model is able to improve the integer count operations skills of deaf grade IV students at SLB Kristinia Bitung.